2008
DOI: 10.1139/w08-060
|View full text |Cite
|
Sign up to set email alerts
|

Variation of cell surface hydrophobicity and biofilm formation among genotypes ofCandida albicansandCandida dubliniensisunder antifungal treatment

Abstract: Candida infections are frequently associated with formation of biofilms on artificial medical devices. This work studied variation of cell surface hydrophobicity (CSH) and formation of biofilm in relation to Candida albicans and Candida dubliniensis genotypes and an effect of some conventional antifungal agents on both CSH and biofilm. The 50 isolates of C. albicans and C. dubliniensis were classified into genotypes A, B, C, and D, genotype D being exclusively represented by C. dubliniensis. No significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Therefore, a combination with microscopy is necessary. As expected, all tested strains were able to form a biofilm, but this ability proved to be strain-dependent for both C. albicans as ell as C. dubliniensis, as was previously described by Borecká-Melkusová et al [29]. It is of interest that while C. dubliniensis was able to form as vital biofilm as C. albicans on a polystyrene surface, SEM microscopy revealed a morphological diversity between both spp.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, a combination with microscopy is necessary. As expected, all tested strains were able to form a biofilm, but this ability proved to be strain-dependent for both C. albicans as ell as C. dubliniensis, as was previously described by Borecká-Melkusová et al [29]. It is of interest that while C. dubliniensis was able to form as vital biofilm as C. albicans on a polystyrene surface, SEM microscopy revealed a morphological diversity between both spp.…”
Section: Discussionsupporting
confidence: 81%
“…Although the formation of a biofilm in the environment is a natural process important for the survival of many microorganisms, medical microbiology regards this complex structure as a serious complication during patient treatment or convalescence. Current trends in biofilm studies are aimed at possible ways to eliminate them, mainly via the application of antifungal agents (Kuhn et al , 2002; Al‐Fattani & Douglas, 2004; Seidler et al , 2006; Borecká‐Melkusová & Bujdáková, 2008). However, some authors have published different thoughts on biofilm treatment, such as photodynamic effects (Müller et al , 2007; Dovigo et al , 2009) or using antibodies (Rodier et al , 2003; Fujibayashi et al , 2009; Maza et al , 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the significant phenotypic and genotypic similarities shared between C. albicans and C. dubliniensis , the comparative virulence of the two species is clearly a very complex topic [40,41]. Borecká-Melkusová [42] verified that the biofilm formation in C. albicans was significantly lower than in C. dubliniensis , and Koga-Ito et al [43] observed that the survival rate and dissemination capacity of C. dubliniensis in mice were lower than C. albicans .…”
Section: Discussionmentioning
confidence: 99%